(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Maternal and neonatal morbidity and mortality remain public health concerns. A study on mortality in Kenyan hospitals found that neonates comprise two-thirds of deaths in the pediatric age group (0–13 years). These deaths are caused by preventable conditions or those, which can be managed better if diagnosed early, such as placenta insufficiency, placenta previa, severe fetal growth restriction, congenital abnormalities, multiple pregnancies, and breech presentation; these can all be identified using point-of-care ultrasound (POCUS). Obstetrical ultrasound availability is limited to level 4 and higher facilities, yet most women access lower levels of health care. Implementation of POCUS is currently limited because of a lack of appropriate training, limited scope of practice for frontline workers, and legal framework. Objective: The POCUS project is being undertaken to develop national guidelines to facilitate the roll out and scale-up of obstetrical POCUS. Methods: A collaborative participatory approach is planned for the development of the national POCUS guidelines. The key in this process is the identification of suitable frontline workers who, with adjustment to their scope of practice, appropriate training, implementation of a supervision/referral system, can undertake obstetrical POCUS and gain buy-in from regulatory bodies, the inclusion of voices of relevant stakeholders, and leadership from government. A landscape and stakeholders analysis will also be undertaken as part of the process of the guideline development. Results: Narrative literature review shows that the WHO recommends effective and reliable antenatal ultrasound services to be available to all pregnant women to optimize maternal and newborn health outcomes and at least one ultrasound scan up to 24 weeks of pregnancy. That there are deliberate efforts in Kenya to introduce POCUS with pilot training and implementation. Where obstetrical POCUS is implemented, it is useful in diagnosing fetal malpresentation, placenta previa, congenital malformations, or multiple pregnancies. Appropriate interventions, such as reduction of cesarean delivery, induction of labor, reduction of small for gestational age, low birthweight, preterm birth, and stillbirths, can improve the health outcome of the mother and neonate. There is a need to develop national POCUS guidelines. Conclusions: Implementation of POCUS may be riddled with difficulties, particularly where frontline workers’ current scope of practice may not allow them to perform such procedures, regulatory framework, lack of knowledge, awareness, negative attitude, or behavior. The proposed guidelines will address these barriers.